2018
DOI: 10.1111/jfd.12904
|View full text |Cite
|
Sign up to set email alerts
|

Increased dietary protein‐to‐lipid ratio improves survival during naturally occurring pancreas disease in Atlantic salmon, Salmo salar L.

Abstract: This study demonstrated that increased dietary protein‐to‐lipid ratio (P/L‐ratio) improved survival of farmed Atlantic salmon naturally affected by pancreas disease (PD). In addition to diet, body weight (BW) and delousing mortality prior to the PD outbreak also contributed significantly (p < 0.05) to explain the observed variation in PD‐associated mortality. Subsequent to the PD outbreak, large amount of fish failed to grow and caused thin fish with poor condition (runts). At the end of the trial, significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The occurrence of fillet-black DS after five months in seawater coincides with Bjørgen et al (2019), who proposed that fillet-red DS are acute focal changes that develop into chronic melanized fillet-black DS (Bjørgen et al, 2015). The prevalence of filletblack DS was 43% on average at harvesting, which is higher than former reports for harvest sized salmon (range 8-33%) (Bjørgen et al, 2019;Dessen et al, 2019;Lutfi et al, 2022;Sissener et al, 2016), though our evaluation method was more sensitive.…”
Section: Discussionmentioning
confidence: 57%
“…The occurrence of fillet-black DS after five months in seawater coincides with Bjørgen et al (2019), who proposed that fillet-red DS are acute focal changes that develop into chronic melanized fillet-black DS (Bjørgen et al, 2015). The prevalence of filletblack DS was 43% on average at harvesting, which is higher than former reports for harvest sized salmon (range 8-33%) (Bjørgen et al, 2019;Dessen et al, 2019;Lutfi et al, 2022;Sissener et al, 2016), though our evaluation method was more sensitive.…”
Section: Discussionmentioning
confidence: 57%
“…It has been extensively demonstrated that dietary and environmental challenges influence fish health and can ultimately have a massive impact on growth performance [36], particularly when stress and diseases come into play [37]- [39]. In addition, although no significant differences were found in feed intake for the whole feeding trial period, fish fed the 3.5%…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation for the differences in growth found at the end of our trial could be related to stress induced by a delousing procedure (August 2018) as well as the onset of a CMS outbreak (September 2018). It has been extensively demonstrated that dietary and environmental challenges influence fish health and can ultimately have a massive impact on growth performance (36) , particularly when stress and diseases come into play (37)(38)(39) . In addition, although no significant differences were found in feed intake for the whole feeding trial period, fish fed the 3•5 % EPA and DHA diet, when compared with the other groups, had a higher SFR and showed a tendency to increased feed intake during the last part of the trial suggesting an improved feed utilisation during a stressful period (delousing and CMS outbreak).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma was separated by centrifugation, stored on dry ice and then sent to the Central Laboratory at the Norwegian University of Life Sciences (Oslo, Norway) for analysis of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and alkaline phosphatase (AP) based on the methods described by Tietz (1995). In addition to the mentioned samplings, fish were routinely sampled from all experimental pens at several occasions for analysis of biometric parameters (visceral somatic index referred to as VSI and visceral fat score) and muscle fat content as described by Dessen et al (2018). The specific feeding rate (SFR), condition factor and organ indices were also calculated as described in the mentioned study.…”
Section: Methodsmentioning
confidence: 99%